Efforts To Increase Tempe Slicing Capacity Through The Implementation Of Appropriate Technology Machines For MSMEs In West Surabaya - Pratomo, Tedy; Muharom, Muharom; Kholili, Navik; Nugroho, Alfi; Muchid, Mochammad; Khusna, Dwi (Pengabdian Masyarakat dan Inovasi Teknologi (DIMASTEK), 2023)
Geographically, Indonesia is an agricultural country. It greatly supports agricultural production. So that the quality and commodity of agricultural products (soybean) remains high, it is necessary to have new ideas or ideas, one of which is by processing tempeh chips to become quality. It prompted researchers to develop innovative equipment that can speed up the tempe chopping process by creating an appropriate technology machine that can produce more optimal chopped tempeh compared to the conventional method, which is 30 kg/hour. This appropriate technology machine is implemented in UKM chips tempeh, Sukomanunggal sub-district, Surabaya City. The machine can help speed up the process of chopping tempeh so that production time can be optimally increased.